Pengolahan Tomat Menjadi Saus sebagai Upaya Ketahanan Pangan Pasca Panen Tomat di Pesantren Lakyar Dakwah - Rizkha Rida; Adinda Juwita Nasution; Nurdiana Nurdiana; Riana Puspita; Jufrizal Jufrizal (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2026)
Food security remains a major challenge for Islamic boarding schools with limited land and resources. This community service program aimed to optimize the use of vacant land at the Markaz Penghafal Al-Qur'an of Yayasan Layar Dakwah to improve food security. The implemented methods included raised-bed preparation, selection of superior seeds, and efficient crop maintenance. The results showed that proper land utilization increased food productivity while reducing dependence on external food supplies. Tomatoes achieved the highest productivity at 2.25 kg/m², followed by chili peppers at 1.75 kg/m² and shallots at 1.25 kg/m². To increase the added value of the harvest, female students received training on processing tomatoes into tomato sauce with a longer shelf life, as well as product packaging and marketing techniques. The program enhanced students' skills in post-harvest processing, enabled them to produce value-added products, and created entrepreneurial opportunities that can generate additional income while supporting the food security of the Islamic boarding school.